Process evaluation of PsyCovidApp, a digital tool for mobile devices aimed at protecting the mental health of healthcare professionals during the COVID-19 pandemic: a mixed method study - Fiol-deRoque, Maria A.; Serrano-Ripoll, Maria J.; Mira-Martínez, Sofia; Pastor-Moreno, Guadalupe; Sitges, Carolina; García-Buades, M. Esther; Gervilla, Elena; Garcia-Toro, Mauro; Zamanillo-Campos, Rocío; Ricci-Cabello, Ignacio (Frontiers in Psychology, 2024)
Introduction: PsyCovidApp, a digital intervention aimed at safeguarding the mental health of healthcare workers during the COVID-19 pandemic, demonstrated in a randomized clinical trial to yield significant improvements solely among healthcare workers undergoing psychotherapy or receiving psychotropic medication. Objectives: 1) To identify contextual factors and mechanisms of action that influenced the impact of PsyCovidApp during the aforementioned trial; 2) To pinpoint enhancements for optimizing its efficacy. Materials and Methods: For the first objective, a process evaluation was conducted, amalgamating quantitative techniques (surveying 216 healthcare professionals who had utilized PsyCovidApp during the trial) and qualitative methods (in-depth interviews with 16 healthcare workers). The second objective involved a panel of seven experts, utilizing the RAND-UCLA methodology. Results: The quantitative study (response rate = 40%) revealed that 22% of respondents had not fully accessed the content of PsyCovidApp. The average usage time was 22.7 min/day, being higher (p<0.05) among consumers of psychotropic medications. Contents related to relaxation and mindfulness were most highly rated. Acceptability and usefulness scores ranged between 7.3 – 7.5/10 points, with higher ratings (p<0.05) among women and older healthcare workers. The qualitative study uncovered that the primary barriers to using PsyCovidApp were workload, lack of time, and exhaustion. Its primary mechanisms of action included emotion identification, mental health regulation (e.g., insomnia, intense emotions), and learning of techniques and skills. The expert panel reached a consensus on 29 proposals to optimize PsyCovidApp. Conclusions: The knowledge derived from this study could inform the design and implementation of future similar digital tools.